Government Ideology and Arms Exports - Agnes Brender (University of Hamburg, Institute of Law and Economics (ILE), 2018)
The relationship between ideology and government decisions is a major field of research in economics and political sciences. Particularly the influence of government ideology on security issues of special interest. This paper analyses the relationship between government orientation and arms exports. Therefore, bilateral trade data for conventional weapons is regressed on data of government orientation. The results indicate that left-wing governments are more likely to grant arms export licences than governments of other partisan orientation. The finding is robust to the inclusion of control variables checking for further characteristics of the exporter government. Including interaction terms shows, that left-wing governments care about the human rights protection in importing countries and prefer to export to countries which are not involved in a conflict.
Keywords: F19; F59; H11; 330; Arms trade; government orientation; partisan ideology